How Much Does Utility Access Matter for the Performance of Micro and Small Enterprises? - Grimm, Michael; Hartwig, Renate; Lay, Jann (World Bank, Washington, DC, 2017)
The empirical evidence of the economic benefits of different utilities such as electricity, telecommunications and water is mixed and, in the case of micro and small enterprises, relatively thin. This paper therefore revisits this issue. Based on a unique, albeit cross-sectional, micro data set of informal firms in West-Africa, we find hardly any evidence for a significant contribution of access to different infrastructure services on enterprise performance. This absence of a systematic influence is attributed to the large heterogeneity of activities, motives and resources with which these informal firms operate. However, concentrating on a more homogenous sample of tailors in Ouagadougou, we find that their performance is positively influenced by access to electricity. In conclusion, our findings stress the heterogeneity of the informal sector, implying that a 'one-size-fits all' approach to the development of this sector is of little help.